Emergence of Socialism Oriented International Economic Order - Lobo, Iris (Kathmandu School of Law Review, 2020)
Winston Churchill had once said that ‘Socialism is a philosophy of failure, the creed of ignorance, and the gospel of envy; its inherent virtue is the equal sharing of misery.’ This was the belief that was once upheld staunchly in all its rigidity amongst the majority of the people in the neoliberal world; who believed in their own gospel of free markets and worshipped the deity of deregulation. However, when Covid-19 struck society with ruthlessness, the common people and even the high priests of global capitalism were willing to scrap decades of neoliberal orthodoxy to alleviate the catastrophic effects of the pandemic and the subsequent economic crisis. A conversion was vehemently demanded and socialism was to be their baptism. This paper analyses the journey of socialism from a Pre-Covid-19 society, a Covid-19 riddled society and then its emergence into an internationally observed economic order in a Post-Covid-19 world. For contrary to what Churchill believed, the Covid-19 catalyst, as captured in this paper, resulted in the revelation of the shroud of neoliberalism and the failure of the philosophy of laissez faire, the awakening of ‘class consciousness’ from its slumber of ignorance, and a gospel of collectivism and communal spirit that the working-class were going to take with, moving forward into a socialism oriented Post-Covid-19 society.